The sensitivity and specificity of the social communication questionnaire for autism spectrum with respect to age. Issue 8 (26th November 2015) - Barnard‐Brak, Lucy; Brewer, Adam; Chesnut, Steven; Richman, David; Schaeffer, Anna Marie
Abstract : The age neutrality of the Social Communication Questionnaire (SCQ) was examined as a common screener for ASD. Mixed findings have been reported regarding the recommended cutoff score's ability to accurately classify an individual as at‐risk for autism spectrum disorder (ASD) (sensitivity) versus accurately classifying an individual as not at‐risk for ASD (specificity). With a sample from the National Database for Autism Research, this study examined the SCQ's sensitivity versus specificity. Analyses indicated that the actual sensitivity and specificity scores were lower than initially reported by the creators of the SCQ. Autism Res 2016, 9: 838–845 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.